Evidence of validity and reliability of the Spanish version of the children's depression inventory-short in peruvian population [Evidencias de validez y fiabilidad de la versión en español del children's depression inventory-short en población peruana] - Ventura-León, J. (2020)
ABSTRACT The objective of this study was to examine the validity evidence of the Children’s Depression Inventory-Short (CDI-S; Kovacs, 1992), in Peruvian school children. A total of 1059 children between 7 and 12 years old participated (Mean = 9.73, SD = 1.23). The results revealed the existence of two factors related to strong loads in the exploratory factor analysis, which were corroborated by confirmatory factor analysis with good goodness-of-fit indices (CFI ≥ .97, RMSEA ≤ .04). The reliability of the CDI-S, calculated with the internal consistency method, was good in both factors (ω > .80). We conclude that the CDI-S is a valid and reliable measure in Peruvian children and should be interpreted as a test with two factors (Dysphoria and Negative self-esteem), which is consistent with previous empirical and theoretical studies.